Evaluation of clinical outcomes of primary postpartum haemorrhage cases referred to an Upazila health complex - Jafreen, Nafisa; Afroj, Sultana; Ferdousi, Shahana; Billah, Shah M. M.; Sharkar, Ummay S.; Akter, M. Rafi; Siddika, Suraiya; Nahar, Kamrun; Basak, Moumita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Primary postpartum haemorrhage (PPH) is a leading cause of maternal mortality and morbidity, especially in low-resource settings. In Bangladesh, the burden of PPH is exacerbated by limited emergency obstetric care and delayed referral. Understanding the clinical profiles and outcomes of PPH at the primary care level is essential for improving maternal health. This study aimed to evaluate the clinical outcomes and associated risk factors of primary PPH cases referred to a rural Upazila Health Complex in Bangladesh. Methods: A prospective observational study was conducted at the Department of Obstetrics and Gynaecology, Nasirnagar Upazila Health Complex, Brahmanbaria, from July 2022 to June 2024. A total of 75 women with primary PPH were enrolled in this study. Data on sociodemographic characteristics, obstetric history, clinical presentation, and pregnancy-specific risk factors were collected using structured forms. Statistical analyses were performed using statistical package for the social sciences (SPSS) version 25.0, with a significance threshold of p≤0.05. Results: Most participants were aged 21–30 years (48%) and resided in rural areas (86.7%). Uterine atony (78.6%), prolonged labour (60%), and induction of labour (52%) were predominant risk factors. The most common complications were maternal anaemia (84%), hypotension (80%), and birth asphyxia (36%). The clinical presentations were dominated by per-vaginal bleeding (92%) and abdominal pain (40%). Conclusions: Primary PPH in rural settings leads to significant maternal and neonatal complications. Early identification, prompt referral, and improved emergency care infrastructure are important for reducing its impact.